Social and Cognitive Psychology Theories in Understanding COVID-19 as the Pandemic of Blame - Bouguettaya, Ayoub; Walsh, Clare E. C.; Team, Victoria (Frontiers in Psychology, 2022)
When faced with adverse circumstances, there may be a tendency for individuals, agencies, and governments to search for a target to assign blame. Our focus will be on the novel coronavirus (COVID-19) outbreak, where racial groups, political parties, countries, and minorities have been blamed for spreading, producing or creating the virus. Blame—here defined as attributing causality, responsibility, intent, or foresight to someone/something for a fault or wrong—has already begun to damage modern society and medical practice in the context of the COVID-19 outbreak. Evidence from past and current pandemics suggest that this tendency to seek blame affects international relations, promotes unwarranted devaluation of health professionals, and prompts a spike of racism and discrimination. By drawing on social and cognitive psychology theories, we provide a framework that helps to understand (1) the effect of blame in pandemics, (2) when people blame, whom they blame, and (3) how blame detrimentally affects the COVID-19 response. Ultimately, we provide a path to inform health messaging to reduce blaming tendencies, based on social psychological principles for health communication.